PDCA-Based Improvement of Packing Systems to Reduce Double Handling and Downtime in Material Handling Operations - Medi Humaedi; Amalina Putri Salsabila; Ridwan Setiawan; Ade Omar Hidayat; Yudi Prastyo (International Journal of Mechanical, Electrical and Civil Engineering, 2026)
An inefficient packing system can result in excessive material handling activities, increased downtime, and higher occupational safety risks. One of the major issues identified in manufacturing operations is double handling, which represents a non-value-added activity that negatively affects operational efficiency. This study aims to improve the packing system by reducing double handling activities, minimizing downtime, and enhancing workplace safety through the implementation of the Plan–Do–Check–Act (PDCA) methodology. Data were collected through direct observation, interviews, and documentation of material handling activities in the production area. Root cause analysis was conducted using a Fishbone Diagram integrated within the PDCA framework to identify the factors contributing to inefficiencies in the existing packing system. Improvement actions included direct pallet utilization, workplace layout optimization, and the addition of towing equipment to facilitate material movement. The results demonstrated significant improvements, with handling activities reduced by 66.7%, handling time reduced by 86.7%, and downtime reduced by 75%. Furthermore, occupational safety risks decreased substantially due to the reduction of manual handling activities. Process capacity also improved, as indicated by the increase in handling frequency from 32 to 240 times per shift. The findings confirm that integrating PDCA with material handling optimization effectively improves operational efficiency, reduces waste, and enhances workplace safety. This study provides practical insights for manufacturing companies seeking to develop more efficient and sustainable packing systems.